Spatial Analysis of Environmental Factors with the Existence of Filariasis Vectors in Brebes Regency - Fadhilla, Shavira Nur; Siwiendrayanti, Arum (Journal of Public Health for Tropical and Coastal Region, 2021)
Introduction: Ketanggungan District is one of the endemic filariasis areas in Brebes Regency since 2016 with a Microfilaria Rate >1%. Filariasis is an infectious disease that attacks the lymph nodes caused by filarial worms and is transmitted by mosquitoes. Environmental factors can affect the transmission of filariasis, which will provide a resting place and breeding place for mosquitoes. Therefore, this research aimed to describe the existence of filariasis vectors and environmental factors that can be seen spatially.Methods: The research was a descriptive observational/ exploratory study using the Geographical Information System (GIS) approach. Data collection was carried out by entomological surveys, subject points sampling, and research objects using GPS. Data were analyzed spatially by Geographic Information Systems (GIS).Results: Culex quinquefasciatus was the type of mosquito which had the highest distribution in the Karangmalang District. The mosquitos were found at sewers, puddles, shrubs, and cattle pens. The vectors can be found within a distance of 29 m to 2 km from filariasis cases.Conclusion: Culex quinquefasciatus may be the vector of filariasis in the Ketanggungan District, with the most environmental factors found in Dukuhturi Village.